Mathematical Abilities in Problem-Solving: analysis of pre-service teachers’ understanding - de Proença, Marcelo Carlos [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of this article is to analyze pre-service mathematics teachers’ understanding of mathematical abilities (MA) in problem-solving. We conducted a qualitative and interpretive study with 15 prospective mathematics teachers from a public state university, who experienced a training course on mathematics teaching through problem-solving. The data were collected through the students' records and audio recordings during the classes. The results showed that, initially, few participants understood what a mathematical ability was, and that there was a failure to differentiate some MA from mathematical knowledge. Throughout the training, the understanding of MA in problem solving broadened, according to their teaching proposals. We conclude that it is important to address this differentiation during initial and continuing education, as well as contextualized situations to favor the development and understanding of MA in problem solving.
Habilidades Matemáticas na Resolução de Problemas: análise da compreensão de futuros professores
Keywords: Initial Training; Mathematical Knowledge; Pedagogical; Teaching Mathematics